Chemical analysis of color change and transcriptional profile in flavonoids biosynthesis during flower development of Tibouchina pulchra (Cham.) Cong. - Rezende, Fernanda Mendes de (2018)
Floral color change is a widespread phenomenon in angiosperms, but poorly understood from the genetic and chemical point of view. This thesis aimed to investigate this phenomenon in Tibouchina pulcha, a native species whose flowers change from white to dark pink. To reach this goal, flavonoid biosynthetic gene expression and compounds were profiled. By using hyphenated techiniques (UPLC-HRMS and NMR), thirty phenolic compounds were quantified and identified, being sixteen described for the first time in T. pulchra. Moreover, an inedite compound was also identified. Five key genes of the flavonoid biosynthetic pathway were partially cloned, sequenced, and the mRNA levels were analyzed (RT-qPCR) along flower development. Collectively, the obtained results demonstrated that the flower color change in T. pulchra is regulated at transcriptional level. Additionally, a metal quantification suggests that Fe3+ ion might influence the saturation of the color at dark pink stage